Detection of Common Beta-thalassemia Mutations by Reverse Dot Blot Analysis - Trang, Nguyen Thu; Ha, Le Thi Thu; Ngan, Nguyen Thuy; Sang, Trieu Tien; Duong, Pham Anh Thuy; Lan, Vo Thi Thuong (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: Beta (β)-thalassemia is the most common genetic disease of anemia caused by mutations on beta globin gene. In Vietnam, there is a high frequency of β -thalassemia carriers with a prevalence ranging from 1.5 to 25.0 % in the different ethnic groups. The most common mutations are the nonsense in codon (CD) 17 (A>T), codon 26 (G>A) and the frameshift at codons 41/42 (-TTCT). The polymerase chain reaction-amplification refractory mutation system (PCR-ARMS) is challenged by using a great number of primer sets for detecting normal and mutated alleles. Reverse dot-blot hybridization using oligonucleotide probes can simultaneously detect allelic specific mutations on a membrane. In this study, we designed oligonucleotide probes specific to the three most common mutations in CD17, CD26 and CD41/42, and used them to optimize hybridization conditions at 68 0 C in 6xSSC hybridization buffer, 2XSSC washing buffer for detecting homozygous or hetezygous alleles of beta globin gene in fifteen individuals of 5 families. Our results were consistent with those detected by PCR-AMRS method, indicating that oligonucleotide probes created by this study was specific, and that the reverse dot-blot hybridization using these oligo probes was convenient for analysis of beta thalassemia disease inVietnam. Keywords : Beta globin gene, beta thalassemia disease,  polymerase chain reaction-amplification refractory mutation system (PCR-ARMS), reverse dot-blot  analysis.